The Model for Managing T-Sports Channel on the Internet (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of the study is to propose the proper management model and the T Sports Channel’s content for theThai context by using the qualitative research by the means of studying the document research and focus group among 20 keyinformants. The purposive sampling was also used for selecting the criteria of those key informants which are as follows: Thegovernor of Sport Authority of Thailand, the director of T Sport Chanel, and those people who are the stakeholders of the TSport Chanel procedure, such as creative directors, organizer and moderators, producers, production technology supervisors,reporters, moderators, the successful sport channel administrators, media academician, sport marketer. The tools for collectingthe data were the document analysis and focus group, and analyzed by content analysis. The result found that the best practicesfor processing 5 T Sport channels on digital TV and the internet system both domestic and international was processing the TSport channels, they should manage the channel for fitting to the sport content, using massive budget for developing theinteresting contents, buying the copyright of broadcasting, broadcasting the popular sport from their own variety channels forapproaching most of the target customers